Os três problemas clássicos da Matemática grega - Freitas, Juliana Martins de [UNESP] (2014)
The fifth and fourth centuries BC were an extremely active period of mathematics in the Greek world. About this period, begin the study of three classical problems of Greek mathematics, which we will address as the main theme. These problems were known as duplicating the cube, trisection of the angle and squaring the circle. Apparently simple statements are geometric problems involving constructions using only not graduate ruler and compass. The study of these three geometric problems challenged the inventive power of numerous mathematicians and intellectuals for over two thousand years, and only in the nineteenth century demonstrated the impossibility of such constructions using only not graduate ruler and compass. In short, the fundamental conception that this work has to provide is the magic of mathematics is not only restricted in the responses of former and current problems, but the new findings, strategies and methods employed arising out of the paths that lead to resolutions. The objective of this paper is to present these three problems, the impossibility of solving them using only not graduated ruler and compass, possible resolutions using other instruments and an application of the doubling cube in the classroom, using origami